Two cases with megalencephalic leukoencephalopathy with subcortical cysts and MLC1 mutations in the Turkish population - Yiş, Uluç; Scheper, Gert C; Uran, Nedret; Unalp, Aycan; Cakmakçi, Handan; Hiz-Kurul, Semra; Dirik, Eray; Van Der Knaap, Marjo S (The Turkish Journal of Pediatrics, 2010)
Megalencephalic leukoencephalopathy with subcortical cysts is a rare leukodystrophy that is characterized by macrocephaly and a slowly progressive clinical course. It is one of the most commonly reported leukoencephalopathies in Turkey. Mutations in the MLC1 gene are the main cause of the disease. We report two patients with megalencephalic leukoencephalopathy with subcortical cysts with confirmed mutations in the MLC1 gene. The mutation in the second patient was novel. We also review identified mutations in the Turkish population.